Investigating the Influence of NEDD4L in the Development of Salt Sensitive Hypertension with Age - Kutcher, Stephen Alexander (Université d'Ottawa / University of Ottawa, 2016)
Background: Hypertension, a leading risk factor for cardiovascular disease, exhibited in 17.7% of the Canadian population, and attributed to 13% of world mortality, is influenced by both the environment and genetics. Salt sensitivity is described at higher rates in the hypertensive population. The NEDD4-like (NEDD4L) protein is important in sodium reabsorption and has been implicated in essential hypertension and salt sensitivity. Objectives: Two variations (rs4149601/rs2288774) found in NEDD4L have been associated with salt sensitivity and hypertension; a third (rs576416) is in linkage disequilibrium with rs4149601. The purpose of this study is to assess the relationship between the NEDD4L rs4149601, rs2288774, and rs576416 single nucleotide polymorphisms with sodium and age on blood pressure (BP). Methods: Canadian hypertensive patients were recruited through the University of Ottawa Heart Institute, with genotyped data from Leuven, Belgium, and the DNA of subjects from Warsaw, Poland also included in the study. Eligible subjects were studied off anti-hypertensive medications. Daytime BP was measured using 24hr ambulatory BP monitoring in 662 Caucasian hypertensives (BP ≥130/85 mmHg). 24hr urine Na+ was collected. DNA from Canada and Poland was genotyped on the GeneTitan Affymetrix Axiom platform and through TaqMan MGB probe-based RT-PCR, while the Belgium samples were analyzed on Illumina 1M-duo arrays. Simple and multivariate linear regression modelling with SAS 9.4.0 was used for genotypic comparisons affecting BP, combined with age and corrected urine sodium. Results: The three hypertensive populations were significantly different (P<0.05) across all demographic and clinical measures, even when stratified by sex. The Polish and female hypertensives from Canada and Belgium were removed from the analysis for lacking the general populations’ trend of increasing BP with age. Multiple linear regressive modelling found a significant association (Pmodel=0.0034) of rs4149601 GA (P=0.0129) and GG (P=0.0082), with age and urine sodium, on SBP in the Belgium male hypertensives (n=273). No significant models analyzing the association of rs576416 and rs2288774 with BP in the Belgium population were found. In the Canadian hypertensive population (n=120) no association on the discrete analyses of the rs4149601, rs576416, and rs2288774 genotypes were found; however the combination of the GG rs4149601 and AA rs576416 (β=0.021, P=0.03) and the GG rs4149601 and CC rs2288774 (β=0.020, P=0.04) genotypes showed significant associations with BP in borderline significant models (P=0.055 and P=0.094 respectively), when analyzed with urine sodium levels and age. Conclusions: A significant influence of the rs4149601 G-allele, with urine sodium and age, was found to be associated with an increase in BP in the Belgium males. Multiple linear modelling describing borderline significant findings in the interaction of rs4149601 with rs576416, and rs4149601 with rs2288774 in Canadian male hypertensives suggests of the possible synergism between polymorphisms and development of salt sensitive hypertension. Future research could evaluate the role of NEDD4L on the sex differences in early-onset salt-sensitive hypertension.
Keywords: NEDD4L; hypertension; salt sensitivity; single nucleotide polymorphisms; personalized medicine; multiple linear regression